Function, digestibility and allergenicity assessment of ovalbumin–EGCG conjugates. (October 2019) - He, Weiyi; Xu, Haoxie; Lu, Yuqin; Zhang, Tingting; Li, Shuiming; Lin, Xiao; Xu, Bingqi; Wu, Xuli
Graphical abstract: Highlights: The OVA–EGCG conjugate was prepared to improve the functional properties of OVA. The covalent conjugation between EGCG and OVA changed the conformation of OVA. OVA increased its digestibility after conjugation with EGCG. The IgE-binding activities of OVA were decreased with EGCG conjugation. The sites of OVA–EGCG conjugation were identified. Abstract: Ovalbumin (OVA) is the major protein in egg white and has multiple functional properties. We prepared the covalent conjugate OVA–(−)-epigallo-catechin 3-gallate (OVA–EGCG) by a radical or alkaline method. LC-MS/MS revealed that EGCG was conjugated with Cys74 and Glu347 in OVA with the radical reaction and with Cys74 in OVA with the alkaline reaction. Multi-spectroscopy studies suggested that OVA unfolded because of its conjugation with EGCG. After conjugation with EGCG, OVA increased its digestibility, antioxidant activity, and emulsifying and foaming properties, with reduced thermal stability. Furthermore, the IgE-binding capacities of OVA were decreased with EGCG conjugation. This work may be helpful for further developing OVA for use in the food industry.